Reflection type mask blank for EUV lithography

The EUV mask blank addresses the challenges of reflectance selectivity and surface smoothness by using a specific composition of Ta and Nb in the absorbing layer, achieving a wide reflectance selectivity and improved etching accuracy for halftone type EUV masks.

JP2025063324APending Publication Date: 2025-04-15AGC INC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2025012247
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-04-21
Filing Date
2025-01-28
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing EUV mask blanks face challenges in achieving a wide reflectance selectivity between 175° to 185°, while maintaining an absorbing layer that is easy to etch and has high surface smoothness, which is crucial for halftone type EUV masks.

Method used

A reflective mask blank for EUV lithography is developed, featuring a reflective layer and an absorbing layer with a composition ratio of Ta:Nb between 4:1 to 1:4, and a half-width FWHM of the peak with the highest intensity being 1.0° or more, which enhances the reflectance selectivity and etching accuracy.

Benefits of technology

The EUV mask blank achieves a wide reflectance selectivity between 175° to 185°, is easy to etch, and has a high surface smoothness, making it suitable for halftone type EUV masks and improving the overall performance in EUV lithography.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063324000004
    Figure 2025063324000004
  • Figure 2025063324000005
    Figure 2025063324000005
  • Figure 2025063324000001
    Figure 2025063324000001
Patent Text Reader

Abstract

To provide an EUV mask blank suitable for halftone type that has a wide range of reflectance selectivity (degree of freedom) at a phase difference of 175 degrees to 185 degrees, as well as that has an absorption layer that is easily etched and has a highly smooth surface.SOLUTION: Provided is a reflection type mask blank for EUV lithography, which is a reflection type mask blank for EUV lithography in which a reflection layer that reflects EUV light and an absorption layer that absorbs the EUV light are formed in this order on a substrate, and is characterized by the fact that the absorption layer contains tantalum (Ta) and niobium (Nb), the composition ratio (at%) of Ta and Nb (Ta:Nb) in the absorption layer (measured by Rutherford backscattering spectroscopy (RBS)) is in the range of 4:1 to 1:4, and among the diffraction peaks derived from the absorption layer observed between 2θ: 20° and 50° in the out-of-plane XRD method, the half-value width FWHM of the highest intensity peak is 1.0° or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a reflective mask blank for EUV (Extreme Ultra Violet) lithography (hereinafter, in this specification, referred to as "EUV mask blank") used in semiconductor manufacturing and the like. [Background technology]

[0002] Conventionally, in the semiconductor industry, photolithography using visible light or ultraviolet light has been used as a transfer technology of fine patterns necessary for forming integrated circuits consisting of fine patterns on Si substrates and the like. However, while the miniaturization of semiconductor devices is accelerating, the limit of conventional photolithography is approaching. In the case of photolithography, the resolution limit of the pattern is about 1 / 2 of the exposure wavelength. Even if the immersion method is used, it is said to be about 1 / 4 of the exposure wavelength, and even if the immersion method of ArF laser (193 nm) is used, the limit is expected to be about 20 nm to 30 nm. Therefore, EUV lithography, an exposure technology using EUV light with an even shorter wavelength than ArF laser, is seen as promising as an exposure technology for 20 nm to 30 nm and beyond. In this specification, EUV light refers to light rays with a wavelength in the soft X-ray region or vacuum ultraviolet region. Specifically, it refers to light rays with a wavelength of about 10 nm to 20 nm, especially about 13.5 nm ± 0.3 nm.

[0003] EUV light is easily absorbed by all materials, and at this wavelength the refractive index of materials is close to 1. This means that refractive optics, as in conventional photolithography using visible or ultraviolet light, cannot be used, and so EUV lithography uses reflective optics, i.e., reflective photomasks and mirrors.

[0004] On the other hand, apart from shortening the wavelength of light, a resolution improvement technique using a phase shift mask has been proposed. A phase shift mask gives a phase difference of 180 degrees to the light transmitted through the transparent parts of a mask pattern by making the transparent parts of the mask pattern out of a different material or shape from the adjacent transparent parts. Therefore, in the region between the two transparent parts, the transmitted diffracted lights with a phase difference of 180 degrees cancel each other out, making the light intensity extremely small, improving the mask contrast, and as a result, the focal depth during transfer is expanded and the transfer accuracy is improved. In principle, a phase difference of 180 degrees is optimal, but a phase difference of about 175 degrees to 185 degrees is sufficient to improve the resolution.

[0005] A halftone mask, which is a type of phase shift mask, is a phase shift mask that uses a thin film that is semi-transparent to the exposure light as an absorption layer for the material that makes up the mask pattern, and attenuates the transmittance to about a few percent (usually about 2.5% to 15.0% for light transmitted through the substrate) while providing a phase difference of about 175 degrees to 185 degrees with respect to light normally transmitted through the substrate, thereby improving the resolution of the pattern edges and improving transfer accuracy.

[0006] Here, the appropriate range of transmittance in a halftone mask will be described. In a conventional halftone mask for an excimer laser, it is desirable to satisfy the optical condition that the transmittance of the absorbing layer is generally 2.5% to 15.0% for ultraviolet light, which is the exposure wavelength. The reason for this is that, first, if the transmittance of the absorbing layer at the exposure wavelength is less than 2.5%, when the diffracted light of light transmitted through adjacent transmitting pattern parts overlaps, the canceling effect becomes small. Conversely, if the transmittance exceeds 15.0%, depending on the exposure conditions, the resolution limit of the resist may be exceeded, and an extra pattern may be formed in the area where the light transmitted through the absorbing layer.

[0007] EUV exposure uses a reflective optical system, has a small NA (numerical aperture), and uses a short wavelength, which means that it is susceptible to surface irregularities on the mirror and mask, making it difficult to accurately resolve the target fine line width. For this reason, a halftone EUV mask has been proposed that makes it possible to apply the principles of halftone masks used in conventional excimer laser exposure and the like to EUV exposure using a reflective optical system (see, for example, Patent Document 1).

[0008] In a reflective mask such as an EUV mask, the principle of improving resolution by the phase shift effect is the same, so the appropriate value is almost the same, except that the above-mentioned "transmittance" is replaced with "reflectance." That is, it is considered desirable that the reflectance of EUV light in the absorbing layer is 2.5% to 15.0%, because this widens the range of selectivity (degree of freedom) of the reflectance when the phase difference between the reflected light of EUV light from the reflective layer and the reflected light of EUV light from the absorbing layer is 175 degrees to 185 degrees (hereinafter, in this specification, this will be referred to as "when the phase difference is 175 degrees to 185 degrees").

[0009] In principle, the use of a half-tone EUV mask is an effective means of improving the resolution in EUV lithography. However, even with a half-tone EUV mask, the optimal reflectance depends on the exposure conditions and the pattern to be transferred, and it is difficult to determine it in general.

[0010] For the above reasons, the absorbing layer in the halftone EUV mask is required to have a wide range (degree of freedom) of selectivity of the reflectance in the phase difference range of 175 degrees to 185 degrees, and at the same time, to be a film that is easily etched. In the invention described in Patent Document 1, by selecting a material containing Ta (tantalum) and Nb (niobium) as the material for the absorption layer, it is possible to achieve a wide range of reflectance selectivity (freedom of choice) while at the same time improving the etching processing accuracy. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] Patent No. 5266988 Summary of the Invention [Problem to be solved by the invention]

[0012] However, it became clear that a compound of Ta and Nb has high crystallinity, and when used as an absorption layer material, it has issues such as high surface roughness of the film and high line edge roughness (LER) after patterning.

[0013] On the other hand, in binary type EUV masks, it is known that the film structure becomes amorphous when nitrides such as TaN or TaBN are used as the absorption layer. However, this is unsuitable for the absorption layer of half-tone type EUV masks because the reflectance for EUV light is too low at less than 2.0%.

[0014] In order to solve the above-mentioned problems of the conventional technology, an object of the present invention is to provide an EUV mask blank suitable for a half-tone EUV mask, which has a wide selectivity (degree of freedom) of reflectance in the phase difference range of 175 degrees to 185 degrees, and at the same time is provided with an absorbing layer that is easy to etch and has a high surface smoothness. [Means for solving the problem]

[0015] In order to achieve the above object, the present inventors have provided a reflective mask blank for EUV lithography, comprising a substrate having a reflective layer that reflects EUV light and an absorbing layer that absorbs EUV light, the reflective layer comprising: the absorption layer contains tantalum (Ta) and niobium (Nb), and the composition ratio (Ta:Nb) of Ta (at%) and Nb (at%) in the absorption layer is in the range of 4:1 to 1:4; The present invention provides a reflective mask blank for EUV lithography, characterized in that the full width at half maximum (FWHM) of the most intense peak among the diffraction peaks originating from the absorbing layer observed at 2θ: 20° to 50° by out of plane XRD method is 1.0° or more. Effect of the Invention

[0016] The EUV mask blank of the present invention has a wide selectivity (degree of freedom) of reflectance in the phase difference range of 175 degrees to 185 degrees, and at the same time has an absorbing layer that is easy to etch and has a high surface smoothness, making it suitable for half-tone EUV masks. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of an EUV mask blank of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another embodiment of the EUV mask blank of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The EUV mask blank of the present invention will now be described with reference to the drawings. Fig. 1 is a schematic cross-sectional view showing one embodiment of an EUV mask blank of the present invention. In an EUV mask blank 1a shown in Fig. 1, a reflective layer 12 that reflects EUV light, a protective layer 13 for the reflective layer 12, and an absorbing layer 14 that absorbs EUV light are formed in this order on a substrate 11. However, in the EUV mask blank of the present invention, of the configuration shown in Fig. 1, only the substrate 11, the reflective layer 12, and the absorbing layer 14 are essential, and the protective layer 13 is an optional component. The protective layer 13 for the reflective layer 12 is a layer provided for the purpose of protecting the reflective layer 12 when the absorbing layer 14 is patterned.

[0019] Hereinafter, the individual components of the EUV mask blank 1a will be described.

[0020] The substrate 11 satisfies the characteristics required for an EUV mask blank substrate. To this end, the substrate 11 has a low thermal expansion coefficient (specifically, a thermal expansion coefficient of 0±0.05×10 at 20° C.). -7 / °C is preferable, and 0±0.03×10 -7 / °C), and has excellent smoothness, flatness, and resistance to cleaning solutions used for cleaning mask blanks or photomasks after pattern formation. Specifically, glass having a low thermal expansion coefficient, such as SiO2-TiO2 glass, is used as the substrate 11, but is not limited thereto, and substrates such as crystallized glass in which a β-quartz solid solution is precipitated, quartz glass, silicon, and metal can also be used. It is preferable that the substrate 11 has a smooth surface with a surface roughness (rms) of 0.15 nm or less and a flatness of 100 nm or less, because this allows high reflectance and transfer accuracy to be obtained in the photomask after pattern formation. The size and thickness of the substrate 11 are appropriately determined based on the design values ​​of the mask, etc. In the embodiment shown later, SiO2-TiO2 glass having an outer shape of 6 inches (152 mm) square and a thickness of 0.25 inches (6.3 mm) was used. It is preferable that there are no defects on the surface of the substrate 11 on which the reflective layer 12 is formed. However, even if defects are present, it is acceptable as long as no phase defects are caused by concave defects and / or convex defects. Specifically, it is preferable that the depth of the concave defect and the height of the convex defect are 2 nm or less, and the half-width of these concave defects and convex defects are 60 nm or less. The half-width of a concave defect refers to the width at a position half the depth of the concave defect. The half-width of a convex defect refers to the width at a position half the height of the convex defect.

[0021] The reflective layer 12 is not particularly limited as long as it has the desired characteristics as a reflective layer of an EUV mask blank. Here, a characteristic that is particularly required for the reflective layer 12 is a high EUV light reflectance. Specifically, when a light beam in the wavelength region of EUV light is irradiated onto the surface of the reflective layer 12 at an incident angle of 6 degrees, the maximum value of the light reflectance at a wavelength of about 13.5 nm is preferably 60% or more, more preferably 65% ​​or more. Even when a protective layer 13 is provided on the reflective layer 12, the maximum value of the light reflectance at a wavelength of about 13.5 nm is preferably 60% or more, more preferably 65% ​​or more.

[0022] As the reflective layer 12, a multilayer reflective film in which high refractive index layers and low refractive index layers are alternately stacked multiple times is usually used because it can achieve a high EUV light reflectance. In the multilayer reflective film forming the reflective layer 12, Mo is widely used for the high refractive index layers, and Si is widely used for the low refractive index layers. That is, a Mo / Si multilayer reflective film is the most common. However, the multilayer reflective film is not limited to this, and Ru / Si multilayer reflective film, Mo / Be multilayer reflective film, Mo compound / Si compound multilayer reflective film, Si / Mo / Ru multilayer reflective film, Si / Mo / Ru / Mo multilayer reflective film, and Si / Ru / Mo / Ru multilayer reflective film can also be used.

[0023] The thickness of each layer constituting the multilayer reflective film constituting the reflective layer 12 and the number of repeat units of the layers can be appropriately selected depending on the film material used and the EUV light reflectance required for the reflective layer. Taking a Mo / Si multilayer reflective film as an example, to obtain a reflective layer 12 with a maximum EUV light reflectance of 60% or more, the multilayer reflective film may be laminated with Mo layers having a thickness of 2.3±0.1 nm and Si layers having a thickness of 4.5±0.1 nm so that the number of repeat units is 30 to 60.

[0024] Each layer constituting the multilayer reflective film forming the reflective layer 12 may be deposited to a desired thickness using a known deposition method such as magnetron sputtering or ion beam sputtering. For example, when forming a Si / Mo multilayer reflective film using ion beam sputtering, a Si target is used as the target, and Ar gas (gas pressure 1.3×10) is used as the sputtering gas. -2 Pa~2.7×10 -2 A Si film was formed to a thickness of 4.5 nm using an ion accelerating voltage of 300 V to 1500 V and a deposition rate of 0.030 nm / sec to 0.300 nm / sec using a 1000 V sputtering gas (gas pressure 1.3 × 10 -2 Pa~2.7×10 -2It is preferable to deposit the Mo film to a thickness of 2.3 nm using a vacuum chamber (1 Pa) at an ion acceleration voltage of 300 V to 1500 V and a deposition rate of 0.030 nm / sec to 0.300 nm / sec. This counts as one cycle, and the Si film and Mo film are laminated 40 to 50 cycles to deposit the Si / Mo multilayer reflective film.

[0025] In order to prevent oxidation of the surface of the reflective layer 12, it is preferable that the top layer of the multilayer reflective film constituting the reflective layer 12 is a layer of a material that is not easily oxidized. The layer of the material that is not easily oxidized functions as a capping layer for the reflective layer 12. A specific example of a layer of a material that is not easily oxidized that functions as a capping layer is a Si layer. When the multilayer reflective film constituting the reflective layer 12 is a Si / Mo multilayer reflective film, the top layer is a Si layer, so that the top layer functions as a capping layer. In this case, the thickness of the capping layer is preferably 11±2 nm.

[0026] The protective layer 13 is provided for the purpose of protecting the reflective layer 12 from damage during the etching process, usually a dry etching process, in which the absorbing layer 14 is patterned. Therefore, a material that is not easily affected by the etching process of the absorbing layer 14, that is, a material that has an etching rate slower than that of the absorbing layer 14 and is not easily damaged by the etching process, is selected as the material for the protective layer. In order to satisfy the above characteristics, the protective layer 13 is preferably made of a material containing ruthenium (Ru). Specific examples of materials containing Ru include Ru and Ru compounds (RuB, RuSi, RuNb, RuTi, RuY, RuZr, RuLa, etc.). The material containing Ru is preferably a material that contains 40.0 at% or more of Ru in the material, more preferably 50.0 at% or more, and even more preferably 55.0 at% or more. The thickness of the protective layer 13 is preferably from 1 nm to 20 nm, and more preferably from 1 nm to 5 nm.

[0027] The protective layer 13 is formed by a known film formation method such as magnetron sputtering or ion beam sputtering. When forming a Ru film by magnetron sputtering, a Ru target is used as the target, and Ar gas (gas pressure 1.0×10) is used as the sputtering gas. -2 Pa~1.0×10 0 It is preferable to form a film to a thickness of 2 nm to 5 nm using a voltage of 30 V to 1500 V and a film formation rate of 0.020 nm / sec to 1.000 nm / sec using a 1000 V DC pressure.

[0028] As described above, the absorbing layer in the halftone EUV mask is required to have a wide selectivity (degree of freedom) of reflectance in the phase difference range of 175 degrees to 185 degrees, and at the same time, to be easy to etch and have a high surface smoothness.

[0029] In the EUV mask blank 1a of the present invention, the absorbing layer 14 contains tantalum (Ta) and niobium (Nb), and the composition ratio (Ta:Nb) of Ta (at%) and Nb (at%) in the absorbing layer 14 measured by Rutherford backscattering spectroscopy (RBS) is in the range of 4:1 to 1:4. The absorbing layer 14 of the above composition has a wide selectivity (degree of freedom) of reflectance at a phase difference of 175 degrees to 185 degrees, and at the same time, has high processing accuracy in etching. If the Nb content is more than the composition ratio (Ta:Nb) of 1:4, the extinction coefficient k of the EUV optical constant becomes low and the EUV reflectance becomes too high, so that sufficient effect as an absorbing layer of a halftone type EUV mask cannot be obtained, and the cleaning solution resistance of the absorbing layer decreases. On the other hand, if the Ta content is more than 4:1 (Ta:Nb), the extinction coefficient k of the EUV optical constant becomes high and the EUV reflectance becomes too low, so that a sufficient effect cannot be obtained as an absorption layer for a halftone EUV mask. The composition ratio of Ta to Nb (Ta:Nb) in the absorption layer 14 is preferably in the range of 3:1 to 1:3, and more preferably in the range of 7:3 to 3:7.

[0030] The absorption layer of the halftone EUV mask preferably has an EUV optical constant with a refractive index n of 0.935 to 0.963 and an extinction coefficient k of 0.008 to 0.030.

[0031] In the EUV mask blank 1a of the present invention, the absorbing layer 14 has the above composition, and in addition, the full width at half maximum (FWHM) of the most intense peak among the diffraction peaks originating from the absorbing layer observed at 2θ: 20° to 50° by out of plane XRD (hereinafter referred to as half width FWHM in this specification) is 1.0° or more. This suppresses crystallinity and increases the smoothness of the surface of the absorbing layer 14. Specifically, the surface roughness (rms) of the surface of the absorbing layer 14 is preferably 0.50 nm or less, more preferably 0.40 nm or less, and further preferably 0.30 nm or less. The absorption layer 14 in the present invention preferably has a half-width FWHM of 2.0° or more, more preferably 3.0° or more. The absorption layer 14 in the present invention preferably has a half-width FWHM of 8.0° or less, more preferably 6.0° or less, and even more preferably 5.0° or less.

[0032] An absorbing layer 14 having a full width at half maximum (FWHM) of 1.0° or more can also be obtained by controlling the deposition conditions during the formation of the absorbing layer 14 . For example, this can be achieved by implementing at least one method selected from the group consisting of increasing the gas pressure, decreasing the input power, and increasing the distance between the sputtering target and the substrate.

[0033] In the EUV mask blank 1a of the present invention, the absorbing layer 14 contains, in addition to Ta and Nb, a predetermined amount of at least one selected from the group consisting of hydrogen (H), boron (B), nitrogen (N) and oxygen (O), thereby obtaining an absorbing layer with a half-width at half maximum (FWHM) of 1.0° or more.

[0034] In the case where the absorbing layer 14 contains B, if the B content in the absorbing layer is 5.0 at % or more, an absorbing layer having a full width at half maximum (FWHM) of 1.0° or more can be obtained. However, if the B content in the absorbing layer is too high, the cleaning solution resistance of the absorbing layer decreases, so that the B content is preferably 20.0 at % or less. The B content in the absorber layer is preferably 7.0 at % to 15.0 at %, and more preferably 8.0 at % to 12.0 at %.

[0035] In the case where the absorbing layer 14 contains N, if the N content in the absorbing layer is 10.0 at % or more, an absorbing layer having a full width at half maximum (FWHM) of 1.0° or more can be obtained. However, if the N content in the absorbing layer is too high, the cleaning solution resistance of the absorbing layer decreases, so that the N content is preferably 35.0 at % or less. The N content in the absorbing layer is more preferably 15.0 at % to 30.0 at %, and further preferably 20.0 at % to 25.0 at %.

[0036] In the case where the absorbing layer 14 contains H, if the H content in the absorbing layer is 0.1 at% or more, an absorbing layer having a full width at half maximum (FWHM) of 1.0° or more can be obtained. However, if the H content in the absorbing layer is too high, the cleaning solution resistance of the absorbing layer decreases, so that the H content is preferably 15.0 at% or less, and more preferably 13.0 at% or less. The H content in the absorbing layer is more preferably 0.1 at % to 10.0 at %, and further preferably 0.1 at % to 8.0 at %.

[0037] When the absorbing layer 14 contains O, if the O content in the absorbing layer is 1.0 at% or more, an absorbing layer with a full width at half maximum (FWHM) of 1.0° or more can be obtained. However, if the O content in the absorbing layer is too high, the following problem occurs. Etching of an absorbing layer containing Ta, such as the absorbing layer 14, is performed in the order of dry etching using a fluorine-based gas and dry etching using a chlorine-based gas not containing oxygen gas. If the O content in the absorbing layer is too high, the etching rate of the dry etching using a chlorine-based gas not containing oxygen drops sharply. Therefore, it is preferable that the O content in the absorbing layer is 20.0 at% or less. The O content in the absorbing layer is more preferably from 2.0 at % to 15.0 at %, and further preferably from 5.0 at % to 10.0 at %.

[0038] In the case where the absorbing layer 14 contains two or more elements selected from the group consisting of H, B, N, and O, by setting the contents of these two or more elements in the absorbing layer within the above ranges, respectively, an absorbing layer having a full width at half maximum (FWHM) of 1.0° or more can be obtained, and the cleaning liquid resistance of the absorbing layer can be improved.

[0039] The absorption layer 14, which contains at least one selected from the group consisting of H, B, N and O in addition to Ta and Nb, can be formed by a known film formation method, for example, a magnetron sputtering method or an ion beam sputtering method.

[0040] When forming an absorption layer containing Ta, Nb, and B by a sputtering method, a sputtering method using a Ta target, an Nb target, and a B target, a sputtering method using a target containing Ta, Nb, and B, a sputtering method using a target containing Ta and Nb and a B target, a sputtering method using a target containing Ta and B and an Nb target, or a sputtering method using a target containing Ta, Nb, and B. When using magnetron sputtering, specifically, it is performed under the following film formation conditions. Sputtering gas: Ar gas (gas pressure 1.0 × 10 -1 Pa~50×10 -1 Pa, preferably 1.0 x 10 -1 Pa~40×10 -1 Pa, more preferably 1.0×10 -1 Pa~30×10 -1 Pa.) Film formation rate: 2.0 nm / min to 60.0 nm / min, preferably 3.5 nm / min to 45.0 nm / min, more preferably 5 nm / min to 30.0 nm / min Input power density per target area: 0.3W / cm2 ~13.0W / cm 2 , preferably 0.6 W / cm 2 ~12.0W / cm 2 , more preferably 1.0 W / cm 2 ~10.0W / cm 2 Distance between target and substrate: 50 mm to 500 mm, preferably 100 mm to 400 mm, more preferably 150 mm to 300 mm

[0041] When forming an absorption layer containing Ta, Nb and N by a sputtering method, a sputtering method using a Ta target and a Nb target, or a sputtering method using a target containing Ta and Nb, may be performed in an atmosphere containing an inert gas and N2. When using a magnetron sputtering method, it may be performed under the following film formation conditions. Sputtering gas: mixed gas of Ar and N (N gas concentration: 1.0 vol% to 80.0 vol%, preferably 2.0 vol% to 75.0 vol%, more preferably 3.0 vol% to 70.0 vol%. Gas pressure: 1.0×10 -1 Pa~50×10 -1 Pa, preferably 1.0 x 10 -1 Pa~40×10 -1 Pa, more preferably 1.0×10 -1 Pa~30×10 -1 Pa.) Film formation rate: 2.0 nm / min to 60.0 nm / min, preferably 3.5 nm / min to 45.0 nm / min, more preferably 5.0 nm / min to 30.0 nm / min Input power density per target area: 0.3W / cm 2 ~13.0W / cm 2 , preferably 0.6 W / cm 2 ~12.0W / cm 2 , more preferably 1.0 W / cm 2 ~10.0W / cm 2 Distance between target and substrate: 50 mm to 500 mm, preferably 100 mm to 400 mm, more preferably 150 mm to 300 mm

[0042] When forming an absorption layer containing Ta, Nb, and H by a sputtering method, a sputtering method using a Ta target and a Nb target, or a sputtering method using a target containing Ta and Nb, may be performed in an atmosphere containing an inert gas and H2. When using a magnetron sputtering method, it may be performed under the following film formation conditions. Sputtering gas: mixed gas of Ar and H (H gas concentration: 1.0 vol% to 80.0 vol%, preferably 2.0 vol% to 75.0 vol%, more preferably 3.0 vol% to 70.0 vol%. Gas pressure: 1.0×10 -1 Pa~50×10 -1 Pa, preferably 1.0 x 10 -1 Pa~40×10 -1 Pa, more preferably 1.0×10 -1 Pa~30×10 -1 Pa.) Film formation rate: 2.0 nm / min to 60.0 nm / min, preferably 3.5 nm / min to 45.0 nm / min, more preferably 5.0 nm / min to 30.0 nm / min Input power density per target area: 0.3W / cm 2 ~13.0W / cm 2 , preferably 0.6 W / cm 2 ~12.0W / cm 2 , more preferably 1.0 W / cm 2 ~10.0W / cm 2 Distance between target and substrate: 50 mm to 500 mm, preferably 100 mm to 400 mm, more preferably 150 mm to 300 mm

[0043] When forming an absorption layer containing Ta, Nb and O by a sputtering method, a sputtering method using a Ta target and a Nb target, or a sputtering method using a target containing Ta and Nb, may be performed in an atmosphere containing an inert gas and O2. When using a magnetron sputtering method, it may be performed under the following film formation conditions. Sputtering gas: mixed gas of Ar and O (O gas concentration: 0.5 vol% to 80.0 vol%, preferably 1.0 vol% to 75.0 vol%, more preferably 2.0 vol% to 70.0 vol%. Gas pressure: 1.0×10 -1 Pa~50×10 -1 Pa, preferably 1.0 x 10 -1 Pa~40×10 -1 Pa, more preferably 1.0×10 -1 Pa~30×10 -1 Pa.) Input power: 30W to 1000W, preferably 50W to 750W, more preferably 80W to 500W Film formation rate: 2.0 nm / min to 60 nm / min, preferably 3.5 nm / min to 45 nm / min, more preferably 5 nm / min to 30 nm / min Input power density per target area: 0.3W / cm 2 ~13.0W / cm 2 , preferably 0.6 W / cm 2 ~11.0W / cm 2 , more preferably 1.0 W / cm 2 ~9.0W / cm 2 Distance between target and substrate: 50 mm to 500 mm, preferably 100 mm to 400 mm, more preferably 150 mm to 300 mm

[0044] The absorbing layer 14 in the EUV mask blank 1a preferably has a film thickness of 50 nm to 75 nm.

[0045] In order to have a wide range (degree of freedom) of selectivity of reflectance at a phase difference of 175 degrees to 185 degrees, when the light reflectance at a wavelength of around 13.5 nm when a light ray in the wavelength region of EUV light is irradiated to the surface of the absorbing layer 14 at an incident angle of 6 degrees is defined as the EUV light reflectance of the absorbing layer surface, and the light reflectance at a wavelength of around 13.5 nm when a light ray in the wavelength region of EUV light is irradiated to the surface of the reflective layer 12 at an incident angle of 6 degrees is defined as the EUV light reflectance of the reflective layer surface, the relative reflectance between the EUV light reflectance of the absorbing layer surface and the EUV light reflectance of the reflective layer surface ((EUV light reflectance of absorbing layer surface / EUV light reflectance of reflective layer surface)×100) is preferably 2.5% to 15.0%. It is preferable that the phase difference between the reflected light of EUV light from the reflective layer 12 and the reflected light of EUV light from the absorbing layer 14 be 175 degrees to 185 degrees, since this maximizes the effect as a phase shift mask. However, as long as the phase difference between the reflected light of EUV light from the reflective layer 12 and the reflected light of EUV light from the absorbing layer 14 is 150 degrees to 220 degrees, the effect as a phase shift mask can be obtained.

[0046] The EUV mask blank 1a of the present invention has a high smoothness of the surface of the absorber layer 14. Specifically, the surface roughness (rms) of the absorber layer 14 surface is preferably 0.50 nm or less, more preferably 0.40 nm or less, and even more preferably 0.30 nm or less. In addition, the surface roughness (rms) of the absorber layer 14 surface is preferably 0.01 nm or more. In the examples described later, the surface roughness (rms) of the surface of the absorbing layer 14 is measured using an atomic force microscope, but the surface roughness (rms) can also be measured based on JIS-B0601-2001.

[0047] In general, half-tone EUV masks are repeatedly cleaned with cleaning solutions containing acids, alkalis, etc., both during the manufacturing process and during use in exposure. In the EUV mask blank 1a of the present invention, it is preferable that the absorbing layer 14 has high cleaning solution resistance. Specifically, when an SPM resistance test is performed twice according to the procedure described in the Examples below, it is preferable that the amount of reduction of the absorbing layer 14 is 0.50 nm or less.

[0048] Since the higher the density of the absorbing layer, the higher the cleaning solution resistance tends to be, the EUV mask blank 1a of the present invention has an absorbing layer 14 with a density of 10.0 g / cm 3 ~15.0g / cm 3 is preferred.

[0049] Since a higher flatness leads to a higher EUV light reflectance and transfer accuracy in the photomask after pattern formation, the flatness (total bow) of the surface on which the absorbing layer 14 is formed in the EUV mask blank 1a of the present invention is preferably 300 nm or less. The flatness of the EUV mask blank can be measured, for example, by a flatness measuring device manufactured by Fujinon Corporation.

[0050] Fig. 2 is a schematic cross-sectional view showing another embodiment of the EUV mask blank of the present invention. In the EUV mask blank 1b shown in Fig. 2, a reflective layer 12 that reflects EUV light, a protective layer 13 for the reflective layer 12, an absorbing layer 14 that absorbs EUV light, a low reflective layer 15 with respect to an inspection light used for inspecting a mask pattern, and a hard mask layer 16 are formed in this order on a substrate 11. Of the components of the EUV mask blank 1b, the substrate 11, the reflective layer 12, the protective layer 13, and the absorbing layer 14 are the same as those of the above-mentioned EUV mask blank 1a, and therefore will not be described.

[0051] The low reflection layer 15 is composed of a film that is low reflective in the inspection light used for inspecting the mask pattern. When manufacturing an EUV mask, after forming a pattern on the absorbing layer, it is inspected whether the pattern is formed as designed. In the inspection of this mask pattern, light with a wavelength of about 190 to 260 nm is usually used as the inspection light. That is, the inspection is performed based on the difference in reflectance of the light with a wavelength of about 190 to 260 nm, specifically, the difference in reflectance between the surface of the absorbing layer 14 that is removed and exposed by pattern formation and the surface of the absorbing layer 14 that is not removed by pattern formation and remains. Here, the former is the surface of the reflective layer 12 or the surface of the protective layer 13. Therefore, if the difference in reflectance between the surface of the reflective layer 12 or the protective layer 13 and the surface of the absorbing layer 14 for the wavelength of the inspection light is small, the contrast during inspection becomes poor, and accurate inspection cannot be performed.

[0052] The absorbent layer 14 having the above-mentioned configuration does not necessarily have a sufficiently low light reflectance when viewed with respect to the wavelength of the inspection light. As a result, the difference between the reflectance of the surface of the absorbent layer 14 at the wavelength of the inspection light and the reflectance of the surface of the reflective layer 12 or the protective layer 13 becomes small, and there is a possibility that sufficient contrast cannot be obtained during inspection. If sufficient contrast cannot be obtained during inspection, pattern defects cannot be sufficiently identified during mask inspection, and accurate defect inspection cannot be performed.

[0053] In the EUV mask blank 1b of the present invention, if a low reflection layer 15 for inspection light is formed on the absorbing layer 14, the light reflectance at the wavelength of the inspection light becomes extremely low, resulting in good contrast during inspection.

[0054] In order to achieve the above characteristics, the low reflection layer 15 is made of a material having a lower refractive index at the wavelength of the inspection light than the absorption layer 14 .

[0055] In order to achieve the above characteristics, in the EUV mask blank 1b of the present invention, it is preferable to use a material containing Ta and O as a constituent material of the low reflective layer 15.

[0056] The material containing Ta and O used for the low reflective layer 15 may contain the above-mentioned other elements in addition to Ta and O. Specific examples of the material containing the above-mentioned other elements in addition to Ta and O include Nb, B, and N.

[0057] When the low reflective layer 15 is formed on the absorbing layer 14, the total thickness of the two is preferably 50 nm to 75 nm.

[0058] The low reflection layer 15 having the above-mentioned structure can be formed by a known film formation method, for example, magnetron sputtering or ion beam sputtering. For example, when a TaONH film is formed as the low reflection layer 15 by magnetron sputtering, a Ta target is used as the target, and a mixed gas of Ar and O2 (H2 gas concentration 1.0 vol% to 50.0 vol%, O2 gas concentration 1.0 vol% to 80.0 vol%, N2 gas concentration 1.0 vol% to 80.0 vol%, Ar gas concentration 5.0 vol% to 95.0 vol%, gas pressure 1.0 × 10 -1 Pa~5.0×10 0 It is preferable to form a film with a thickness of 1.5 nm to 30 nm using a vacuum chamber (100 Pa) at an input power of 30 W to 3000 W, a film formation rate of 0.01 nm / min to 60 nm / min. When an inert gas other than Ar is used, the concentration of the inert gas is set in the same concentration range as the above-mentioned Ar gas concentration.

[0059] In the EUV mask blank 1b, when the surface of the low-reflective layer 15 is irradiated with light in the wavelength region of EUV light at an incident angle of 6 degrees, the light reflectance at a wavelength of around 13.5 nm is defined as the EUV light reflectance of the low-reflective layer surface. The relative reflectance between the EUV light reflectance of the low-reflective layer surface and the EUV light reflectance of the reflective layer surface ((EUV light reflectance of low-reflective layer surface / EUV light reflectance of reflective layer surface)×100) is preferably 2.5% to 15.0%. In the EUV mask blank 1b, a phase difference between the reflected light of EUV light from the reflective layer 12 and the reflected light of EUV light from the low reflective layer 15 of 175 degrees to 185 degrees is preferable because this provides a sufficient effect as a phase shift mask, but the effect as a phase shift mask can be obtained if the phase difference between the reflected light of EUV light from the reflective layer 12 and the reflected light of EUV light from the low reflective layer 15 is 150 degrees to 220 degrees.

[0060] In the EUV mask blank 1b of the present invention, the surface roughness (rms) of the low reflective layer 15 is preferably 0.50 nm or less, more preferably 0.40 nm or less, and even more preferably 0.30 nm or less. The surface roughness (rms) of the low reflective layer 15 is preferably 0.01 nm or more.

[0061] In the EUV mask blank 1b of the present invention, the density of the low reflective layer 15 is 5.0 g / cm 3 ~8.5g / cm 3 is preferred, and 5.0 g / cm 3 ~8.2g / cm 3 is more preferred.

[0062] In the EUV mask blank 1b of the present invention, the reason why the low reflective layer 15 is preferably formed on the absorbing layer 14 is because the wavelength of the pattern inspection light is different from the wavelength of the EUV light. Therefore, when EUV light (wavelength of about 13.5 nm) is used as the pattern inspection light, it is considered that it is not necessary to form the low reflective layer 15 on the absorbing layer 14. The wavelength of the inspection light tends to shift to the short wavelength side as the pattern dimensions become smaller, and is considered to shift to 193 nm and further to 13.5 nm in the future. When the wavelength of the inspection light is 13.5 nm, it is considered that it is not necessary to form the low reflective layer 15 on the absorbing layer 14.

[0063] The hard mask layer 16 is required to have a sufficiently high etching selectivity under the etching conditions for the absorber layer 14 and the low reflective layer 15. To achieve this, the hard mask layer 16 needs to have sufficient etching resistance against the etching conditions for the absorber layer 14 and the low reflective layer 15. As described above, when the absorbing layer or the low-reflecting layer is made of a material containing Ta, the etching of the absorbing layer is performed in the order of dry etching using a fluorine-based gas and dry etching using a chlorine-based gas not containing oxygen gas. Therefore, the hard mask layer 16 is required to have high etching resistance against dry etching using a fluorine-based gas and dry etching using a chlorine-based gas not containing oxygen gas.

[0064] In order to satisfy the above-mentioned requirements, the hard mask layer 16 of the EUV mask blank 1b of the present invention contains chromium (Cr) and at least one selected from the group consisting of N and O. Specific examples include a CrN film containing Cr and N, a CrO film containing Cr and O, and a CrON film containing Cr, O and N.

[0065] The film thickness of the hard mask layer 16 is preferably from 2 nm to 30 nm, more preferably from 2 nm to 25 nm, and further preferably from 2 to 10 nm.

[0066] The hard mask layer 16 can be formed by a known film forming method, for example, a sputtering method such as magnetron sputtering or ion beam sputtering.

[0067] When forming a CrO film by sputtering, sputtering may be performed using a Cr target in an atmosphere containing an inert gas containing at least one of He, Ar, Ne, Kr, and Xe (hereinafter simply referred to as an inert gas) and O2 gas. When using magnetron sputtering, the film may be formed under the following film formation conditions. Sputtering gas: Ar and O2 mixed gas O2 gas concentration: 15.0 vol% to 100.0 vol%, preferably 20.0 vol% to 80.0 vol% Ar gas concentration: 0.0 vol% to 85.0 vol%, preferably 20.0 vol% to 80.0 vol% Gas pressure 5.0 x 10 -2 ~1.0×10 0Pa, preferably 1.0 x 10 -1 ~8.0×10 -1 Pa, more preferably 2.0×10 -1 ~4.0×10 -1 Pa Input power density per target area: 2.0W / cm 2 ~13.0W / cm 2 , preferably 3.0 W / cm 2 ~12.0W / cm 2 , more preferably 4.0 W / cm 2 ~10.0W / cm 2 Film formation rate: 0.010 nm / sec to 0.400 nm / sec, preferably 0.015 nm / sec to 0.300 nm / sec, more preferably 0.020 nm / sec to 0.200 nm / sec Distance between target and substrate: 50 mm to 500 mm, preferably 100 mm to 400 mm, more preferably 150 mm to 300 mm

[0068] When forming a CrN film by sputtering, sputtering may be performed using a Cr target in an atmosphere containing an inert gas and N. When using magnetron sputtering, the film may be formed under the following film formation conditions. Sputtering gas: Ar and N2 mixed gas N2 gas concentration: 15.0 vol% to 100.0 vol%, preferably 20.0 vol% to 80.0 vol% Ar gas concentration: 0.0 vol% to 85.0 vol%, preferably 20.0 vol% to 80.0 vol% Gas pressure 5.0 x 10 -2 Pa~1.0×10 0 Pa, preferably 1.0 x 10 -1 Pa~8.0×10 -1 Pa, more preferably 2.0×10 -1 Pa ~ 4.0 × 10 -1 Pa Input power density per target area: 2.0W / cm 2 ~13.0W / cm 2 , preferably 3.0 W / cm 2~12.0W / cm 2 , more preferably 4.0 W / cm 2 ~10.0W / cm 2 Film formation rate: 0.010 nm / sec to 0.400 nm / sec, preferably 0.015 nm / sec to 0.300 nm / sec, more preferably 0.020 nm / sec to 0.200 nm / sec Distance between target and substrate: 50 mm to 500 mm, preferably 100 mm to 400 mm, more preferably 150 mm to 300 mm

[0069] When forming a CrON film by sputtering, sputtering may be performed using a Cr target in an atmosphere containing an inert gas, O2, and N2. When using magnetron sputtering, the film may be formed under the following film formation conditions. Sputtering gas: Ar, O2 and N2 mixed gas N2 gas concentration: 14.9 vol% to 99.9 vol%, preferably 20.0 vol% to 80.0 vol% O2 gas concentration: 0.1 vol% to 85.0 vol%, preferably 0.5 vol% to 80.0 vol% Ar gas concentration: 0.0 vol% to 85.0 vol%, preferably 20.0 vol% to 80.0 vol% Gas pressure 5.0 x 10 -2 Pa~1.0×10 0 Pa, preferably 1.0 x 10 -1 Pa~8.0×10 -1 Pa, more preferably 2.0×10 -1 Pa ~ 4.0 × 10 -1 Pa Input power density per target area: 2.0W / cm 2 ~13.0W / cm 2 , preferably 3.0 W / cm 2 ~12.0W / cm 2 , more preferably 4.0 W / cm 2 ~10.0W / cm 2 Film formation rate: 0.010 nm / sec to 0.400 nm / sec, preferably 0.015 nm / sec to 0.300 nm / sec, more preferably 0.020 nm / sec to 0.200 nm / sec Distance between target and substrate: 50 mm to 500 mm, preferably 100 mm to 400 mm, more preferably 150 mm to 300 mm

[0070] When an inert gas other than Ar is used, the concentration of the inert gas is set to be in the same concentration range as the Ar gas concentration described above. When multiple types of inert gas are used, the total concentration of the inert gas is set to be in the same concentration range as the Ar gas concentration described above.

[0071] In the EUV mask blank 1b of the present invention, the flatness (total bow) of the surface on which the hard mask layer 16 is formed is preferably 300 nm or less.

[0072] The EUV mask blanks 1a and 1b of the present invention may have a functional film known in the field of EUV mask blanks in addition to the reflective layer 12, protective layer 13, absorbing layer 14, low reflective layer 15, hard mask layer 16, and a protective layer formed as necessary. A specific example of such a functional film is a high dielectric coating applied to the back side of the substrate to promote electrostatic chucking of the substrate, as described in JP-T-2003-501823. Here, the back side of the substrate refers to the surface of the substrate 11 in FIG. 1 opposite to the side on which the reflective layer 12 is formed. The high dielectric coating applied to the back side of the substrate for such a purpose is selected so that the electrical conductivity and thickness of the constituent material are such that the sheet resistance is 100Ω / □ or less. The constituent material of the high dielectric coating can be widely selected from those described in known documents. For example, a high dielectric constant coating described in JP-T-2003-501823, specifically a coating made of silicon, TiN, molybdenum, chromium, or TaSi, can be applied. The thickness of the high dielectric coating can be, for example, 10 to 1000 nm. The high dielectric coating can be formed by using a known film formation method, for example, a sputtering method such as magnetron sputtering or ion beam sputtering, a CVD method, a vacuum deposition method, or an electrolytic plating method. EXAMPLES

[0073] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples. Among Examples 1 to 8, Examples 1, 6 to 7 are Comparative Examples, and Examples 2 to 5 and 8 are Examples.

[0074] Example 1 In Example 1, an EUV mask blank 1a shown in FIG. 1 is produced. A SiO2-TiO2-based glass substrate (6-inch (152 mm) square, 6.3 mm thick) is used as the substrate 11 for film formation. The thermal expansion coefficient of this glass substrate at 20°C is 0.02×10 -7 / ℃, Young's modulus is 67GPa, Poisson's ratio is 0.17, and specific rigidity is 3.07×10 7 m 2 / s 2 The glass substrate is polished to have a smooth surface with a surface roughness (rms) of 0.15 nm or less and a flatness of 100 nm or less.

[0075] On the back surface side of the substrate 11, a 100 nm thick Cr film is formed by magnetron sputtering, thereby providing a high dielectric coating with a sheet resistance of 100 Ω / □. The substrate 11 (6-inch (152 mm) square outer shape, 6.3 mm thick) is fixed to a normal flat electrostatic chuck via the formed Cr film, and Si films and Mo films are alternately formed on the surface of the substrate 11 using ion beam sputtering, and this process is repeated 40 times to form a Si / Mo multilayer reflective film (reflective layer 12) with a total thickness of 272 nm ((4.5 nm + 2.3 nm) × 40). Furthermore, a Ru film (thickness: 2.5 nm) is formed on the Si / Mo multilayer reflective film (reflective layer 12) by ion beam sputtering, thereby forming a protective layer 13.

[0076] The deposition conditions for the Si film, Mo film and Ru film are as follows. Si film deposition conditions Target: Si target (boron doped) Sputtering gas: Ar gas (gas pressure 2.0 × 10 -2 Pa) Voltage: 700V Deposition rate: 0.077nm / sec Film thickness: 4.5 nm Mo film deposition conditions Target: Mo target Sputtering gas: Ar gas (gas pressure 2.0 × 10 -2 Pa) Voltage: 700V Deposition rate: 0.064nm / sec Film thickness: 2.3 nm Ru film deposition conditions Target: Ru target Sputtering gas: Ar gas (gas pressure 2.0 × 10 -2 Pa) Voltage: 500V Deposition rate: 0.023nm / sec Film thickness: 2.5 nm

[0077] Next, the absorption layer 14 (TaNb film) containing Ta and Nb is formed on the protective layer by magnetron sputtering under the following film forming conditions. Conditions for forming the absorption layer 14 (TaNb film) Target: Ta target, Nb target Sputtering gas: Ar gas (gas pressure: 4.0 × 10 -1 Pa) Input power density per Ta target area: 8.0 W / cm 2 Distance between Ta target and substrate: 300 mm Input power density per Nb target area: 5.8W / cm 2 Distance between Nb target and substrate: 300 mm Deposition speed: 5.0nm / min Film thickness: 59 nm

[0078] The EUV mask blank 1a obtained by the above procedure is subjected to the following evaluations (1) to (7). The same evaluation results can be obtained for the following evaluations (1) to (7) when an absorber layer (TaNb film) is formed on a silicon wafer.

[0079] (1) Film composition The composition of the absorbing layer (TaNb film) is measured using a Rutherford Back Scattering Spectroscopy (manufactured by Kobe Steel, Ltd.) The composition ratio (at%) of the absorbing layer (TaNb film) is Ta:Nb=65.0:35.0. In this embodiment, the composition ratio of the absorber layer is measured using a Rutherford backscattering spectrometer. However, the composition ratio of the absorber layer can also be measured by other measurement methods such as X-ray photoelectron spectroscopy (XPS) and energy dispersive X-ray analysis (EDX).

[0080] (2) Film thickness and film density The thickness and film density of the absorbing layer (TaNb film) are measured by X-ray reflectometry (XRR).

[0081] (3) Calculation of phase difference and relative reflectance in the EUV wavelength region The phase difference between the EUV light reflected from the reflective layer 12 and the EUV light reflected from the absorbing layer 14, and the relative reflectance between the EUV light reflectance of the surface of the absorbing layer 14 and the EUV light reflectance of the surface of the reflective layer 12 are obtained by optical simulation. The optical constants of the reflective layer required for the simulation use values ​​from the database of the Center for X-Ray Optics, Lawrence Berkeley National Laboratory. In addition, the optical constants of the absorbing layer are evaluated by measuring the "angle dependency" of the reflectance in the 13.5 nm region. Specifically, the EUV reflectance, the angle of incidence of EUV light, and the optical constants are expressed by the following equations. R = |(sinθ-((n+ik) 2-cos 2 θ) 1 / 2 ) / (sinθ+((n+ik) 2 -cos 2 θ) 1 / 2 )| Here, θ is the incident angle of the EUV light, R is the EUV reflectance at the incident angle θ, n is the refractive index of the absorbing layer, and k is the extinction coefficient of the absorbing layer. The EUV optical constants (refractive index (n), extinction coefficient (k)) can be estimated by fitting the measured reflectance at each EUV incident angle using the above formula.

[0082] (4) Crystalline peaks originating from the absorption layer The absorption layer (TaNb film) is measured by the out of plane XRD method. The full width at half maximum (FWHM) is calculated for the peak with the highest intensity among the diffraction peaks originating from the absorption layer observed at 2θ: 20° to 50°.

[0083] (5) SPM resistance The absorber layer (TaNb film) was immersed in 100°C SPM (sulfuric acid / hydrogen peroxide mixture, sulfuric acid:hydrogen peroxide solution = 3:1) for 20 minutes, and then rinsed with pure water. The film thickness was measured before and after immersion in SPM to determine the change in film thickness before and after immersion. In the table below, positive values ​​indicate a decrease in film thickness, and negative values ​​indicate an increase in film thickness. The SPM resistance test is performed twice.

[0084] (6) Surface roughness (rms) The surface roughness (rms) of the absorption layer (TaNb film) surface is measured using an atomic force microscope.

[0085] (7) Cl2 etching rate A sample with an absorbing layer (TaNb film) is placed on the sample stage of an ICP (inductively coupled plasma) etching device, and ICP plasma etching is performed under the conditions shown below to determine the etching rate. ICP antenna bias: 200W Substrate bias: 40W Etching time: 30 sec Trigger pressure: 5.0×10 0 Pa Etching pressure: 3.0×10 -1 Pa Etching gas: Cl2 / He Gas flow rate (Cl2 / He): 4 / 16sccm

[0086] Example 2 Example 2 is carried out in the same manner as Example 1, except that an absorption layer (TaNbB film) containing Ta, Nb and B is formed as the absorption layer 14 under the following conditions. Deposition conditions of the absorption layer (TaNbB film) Target: TaB (Ta:B = 60:40) target, Nb target Sputtering gas: Ar gas (gas pressure: 2.2 × 10 -1 Pa) Input power density per TaB target area: 6.4W / cm 2 Distance between TaB target and substrate: 150mm Input power density per Nb target area: 4.7W / cm 2 Distance between Nb target and substrate: 150 mm Deposition speed: 14.0nm / min Film thickness: 59 nm

[0087] Example 3 Example 3 is carried out in the same manner as Example 1, except that an absorption layer (TaNbB film) containing Ta, Nb and B was formed as the absorption layer 14 under the following conditions. Deposition conditions of the absorption layer (TaNbB film) Target: TaB (Ta:B = 60:40) target, Nb target Sputtering gas: Ar gas (gas pressure: 2.2 × 10 -1 Pa) Input power density per TaB target area: 9.9W / cm 2 Distance between TaB target and substrate: 150mm Input power density per Nb target area: 2.5W / cm 2 Distance between Nb target and substrate: 150 mm Deposition speed: 7.6nm / min Film thickness: 59 nm

[0088] Example 4 Example 4 is carried out in the same manner as Example 1, except that an absorption layer (TaNbN film) containing Ta, Nb and N was formed as the absorption layer 14 under the following conditions. Deposition conditions of the absorption layer (TaNbN film) Target: Ta target, Nb target Sputtering gas: Ar and N2 mixed gas (Ar: 96.2 vol%, N2: 3.8 vol%, gas pressure: 2.2 × 10 -1 Pa) Input power density per Ta target area: 9.9 W / cm 2 Distance between Ta target and substrate: 150 mm Input power density per Nb target area: 7.4W / cm 2 Distance between Nb target and substrate: 150 mm Deposition speed: 24.8nm / min Film thickness: 59 nm

[0089] Example 5 Example 5 is carried out in the same manner as Example 1, except that an absorption layer (TaNbN film) containing Ta, Nb and N was formed as the absorption layer 14 under the following conditions. Deposition conditions of the absorption layer (TaNbN film) Target: Ta target, Nb target Sputtering gas: Ar and N2 mixed gas (Ar: 90.0 vol%, N2: 10.0 vol%, gas pressure: 2.2 × 10 -1 Pa) Input power density per Ta target area: 9.9 W / cm 2 Distance between Ta target and substrate: 150 mm Input power density per Nb target area: 7.4W / cm 2 Distance between Nb target and substrate: 150 mm Deposition speed: 26.9nm / min Film thickness: 59 nm

[0090] Example 6 Example 6 is carried out in the same manner as Example 1, except that an absorption layer (TaN film) containing Ta and N was formed as the absorption layer 14 under the following conditions. Conditions for forming the absorption layer (TaN film) Target: Ta target Sputtering gas: mixed gas of Ar, Kr and N2 (Ar: 43.0 vol%, Kr: 43.0 vol%, N2: 14.0 vol%, gas pressure: 2.6 × 10 -1 Pa) Input power density per target area: 9.9W / cm 2 Distance between target and board: 150mm Deposition speed: 14.2nm / min Film thickness: 60nm

[0091] Example 7 Example 7 is carried out in the same manner as Example 1, except that an absorption layer containing Ta, B and N (TaBN film) is formed as the absorption layer 14. Conditions for forming the absorption layer (TaBN film) Target: TaB (Ta:B = 60:40) target Sputtering gas: Ar and N2 mixed gas (Ar: 80.0 vol%, N2: 20.0 vol%, gas pressure: 2.2 × 10 -1 Pa) Input power density per target area: 9.9W / cm 2 Distance between target and board: 150mm Deposition speed: 14.4nm / min Film thickness: 60nm

[0092] Example 8 Example 8 is carried out in the same manner as Example 1, except that an absorption layer containing Ta, Nb and O (TaNbO film) is formed as the absorption layer 14. Conditions for forming the absorption layer (TaNbO film) Target: Ta target, Nb target Sputtering gas: Ar and O2 mixed gas (Ar: 97.9 vol%, O2: 2.1 vol%, gas pressure: 2.2 × 10 -1 Pa) Input power density per Ta target area: 9.9 W / cm 2 Distance between Ta target and substrate: 150 mm Input power density per Nb target area: 8.9W / cm 2 Distance between Nb target and substrate: 150 mm Deposition speed: 18.8nm / min Film thickness: 59 nm

[0093] [Table 1]

[0094] [Table 2]

[0095] [Table 3]

[0096] In Example 1 where the half width FWHM is less than 1.0°, the surface roughness of the absorbing layer surface exceeds 0.50 nm. In Examples 2 to 5 and 8 where the half width FWHM is 1.0° or more, the surface roughness of the absorbing layer surface is 0.50 nm or less. The SPM resistance is excellent in Example 2, in which the absorbing layer 14 contains 5.0 to 20.0 at % B, Example 4, in which the absorbing layer 14 contains 10.0 to 35.0 at % N, and Example 8, in which the absorbing layer 14 contains 1.0 to 20.0 at % O. Moreover, Example 7, which is a TaBN film, has poor SPM resistance. In the TaN film example 6 and the TaBN film example 7, the relative reflectance between the EUV light reflectance of the absorber layer 14 surface and the EUV light reflectance of the reflective layer 12 surface is less than 2.5%, which is too low, and therefore these are unsuitable for the absorber layer of a half-tone EUV mask. [Explanation of symbols]

[0097] 1: EUV mask blank 11: Substrate 12: Reflective layer (multilayer reflective film) 13:Protective layer 14: Absorption layer 15:Low reflective layer 16: Hard mask layer

Claims

1. A reflective mask blank for EUV lithography, comprising a substrate having a reflective layer that reflects EUV light and an absorbing layer that absorbs EUV light formed in this order on the substrate, The absorbing layer contains tantalum (Ta) and niobium (Nb), the full width at half maximum (FWHM) of the most intense peak among the diffraction peaks originating from the absorbing layer observed at 2θ: 20° to 50° by an out of plane XRD method is 1.0° or more; a relative reflectance ((EUV light reflectance of absorber layer surface / EUV light reflectance of reflector layer surface)×100) of an EUV light reflectance of the absorber layer surface to an EUV light reflectance of the reflector layer surface is 2.5% to 15.0%.

2. 2. The reflective mask blank for EUV lithography according to claim 1, wherein the absorbing layer further contains at least one selected from the group consisting of hydrogen (H), boron (B), nitrogen (N) and oxygen (O).

3. 3. The reflective mask blank for EUV lithography according to claim 2, wherein the absorber layer contains B in an amount of 5.0 to 20.0 at %.

4. 4. The reflective mask blank for EUV lithography according to claim 2, wherein the absorber layer contains 10.0 to 35.0 at % N.

5. 5. The reflective mask blank for EUV lithography according to claim 2, wherein the absorber layer contains 0.1 to 15.0 at % of H.

6. 6. The reflective mask blank for EUV lithography according to claim 2, wherein the absorber layer contains 1.0 to 20.0 at % O.

7. 7. The reflective mask blank for EUV lithography according to claim 1, wherein the absorbing layer has an EUV optical constant having a refractive index of 0.935 to 0.963 and an extinction coefficient of 0.008 to 0.

030.

8. 8. The reflective mask blank for EUV lithography according to claim 1, wherein a phase difference between light of EUV light reflected from the reflective layer and light of EUV light reflected from the absorber layer is 150 degrees to 220 degrees.

9. 9. The reflective mask blank for EUV lithography according to claim 1, wherein the surface roughness (rms) of the absorber layer surface is 0.50 nm or less.

10. 10. The reflective mask blank for EUV lithography according to claim 1, further comprising a hard mask layer on the absorbing layer, the hard mask layer containing chromium (Cr) and at least one selected from the group consisting of nitrogen (N) and oxygen (O).

11. 8. The reflective mask blank for EUV lithography according to claim 1, further comprising a low reflective layer for inspection light (wavelength 190 to 260 nm) for a mask pattern on the absorption layer, the low reflective layer containing tantalum (Ta) and oxygen (O).

12. 12. The reflective mask blank for EUV lithography according to claim 11, wherein a total thickness of the absorber layer and the low reflective layer is 50 to 75 nm.

13. The density of the absorbent layer is 10 to 15 g / cm 3 and the density of the low reflective layer is 5 to 8.2 g / cm 3 The reflective mask blank for EUV lithography according to claim 11 or 12,

14. 14. The reflective mask blank for EUV lithography according to any one of claims 11 to 13, wherein a phase difference between light of EUV light reflected from the reflective layer and light of EUV light reflected from the low reflective layer is 150 degrees to 220 degrees.

15. 15. The reflective mask blank for EUV lithography according to any one of claims 11 to 14, wherein the surface roughness (rms) of the low reflective layer surface is 0.50 nm or less.

16. The reflective mask blank for EUV lithography according to any one of claims 11 to 15, further comprising a hard mask layer on the low reflective layer, the hard mask layer containing chromium (Cr) and at least one selected from the group consisting of nitrogen (N) and oxygen (O).

17. 17. The reflective mask blank for EUV lithography according to claim 1, wherein the flatness of the surface on which the absorber layer is formed is 300 nm or less.

Citation Information

Patent Citations

  • Reflective mask blank for EUV lithography

    JP2007311758A

  • Method for depositing reflective multilayer film of reflective mask blank for EUV lithography and method for producing reflecting mask blank for EUV lithography

    JP2008109060A

  • Halftone-type EUV mask, halftone-type EUV mask blank, production method of halftone-type EUV mask, and pattern transfer method

    JP2010067757A

  • Reflective mask blank, and method of manufacturing reflective mask

    JP2010251490A

  • Reflective mask blank, reflective mask and manufacturing method of semiconductor device

    JP2015122468A